Perkembangan Komunikasi Islam Di Era Moderen - Musliadi, Musliadi; Muhlis, Muhlis (RETORIKA : Jurnal Kajian Komunikasi dan Penyiaran Islam, 2023)
Many innovations occur as a result of the growth of an increasingly evolved and evolving age that transitions from traditional to contemporary times, one of which is the development of Islamic communication. Individuals in society, as well as all parts of culture and social systems, experience social change as a social process in which all levels of community life leave patterns of life, culture, and social systems behind and subsequently adapt. or new social forms of life, culture, and systems. Islamic communication in social transformation must lead to the resolution of real-world issues. Islam, being a kaffah religion, governs all human activity, including communication. Because the lenses used in this work for communication science are Islam, the purpose of the study of communication science, how to gain it, construct it, and its advantages, also employs the teaching approach included in Islam.